Assessing the Levels of Awareness and Implementation Effectiveness of Lean Tools in Furniture Industry: A Case Study Approach - Baraa Hakawati; Hamed Al-Hamadneh; Yahya Saleh (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
The furniture industry faces constant pressure to improve efficiency, reduce costs and maintain product quality. To this end, the furniture industry employs diverse tools in their operations including Lean tools which emphasize waste reduction, process optimization and continuous improvement. This study aims at assessing the levels of awareness, implementation, effectiveness and the future use of Lean tools in Palestinian furniture industry as perceived by its employees. More specifically, a case study of a Palestinian furniture company of 120 employees was selected. A quantitative research method was adopted where the perceptions on Lean tools were collected from a random sample of employees using a self-administered questionnaire. It was found from the analysis that awareness and the future use of Lean tools are of moderate levels, while implementation and effectiveness are, respectively of low and high levels. A real case in the cabinet assembly department of the company was conducted where the states of the department before and after Lean implementation were analyzed. Then, 5S, Just-in-Time and Continuous Flow tools were applied in the department. A set of performance metrics have been measured before and after implementation. The analysis revealed substantial improvements in waste reduction, cost, labor utilization, assembly time and productivity.